(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the effectiveness of irrigation technologies for crops using river and stream waters. Based on research, the advantages of the irrigation method in saving water, increasing productivity, and improving environmental conditions are shown. The scope of application of the technology, existing limitations, and recommendations for its implementation are also covered. The article contains scientific and practical foundations aimed at the rational use of water resources and the development of modern agricultural technologies.